Makna Pappasang dalam Budaya Masyarakat Nelayan Patorani di Desa Mangindara, Kecamatan Galesong Selatan - Nurman, Nadila (Tumanurung: Jurnal Sejarah dan Budaya, 2025)
Patorani, a fisherman who specialises in catching flying fish in Mangindara, South Galesong, and found that pappasang is a provision for Patorani in carrying out torani activities, providing instructions on how to live a life with good morals and morals, as well as providing guidance in facing the challenges and risks faced in the fishing profession. Therefore, this research aims to raise the local cultural values contained in pappasang, as well as provide inspiration for the younger generation to preserve the culture and noble values contained therein. Through a descriptive qualitative method in the form of literature study, this research will reveal how traditions and cultural values are inherited and practised in the daily lives of the people of South Sulawesi, show the important role of pappasang in shaping the character, behaviour and morals of the people of South Sulawesi, and the role of pappasang in understanding and preserving local culture. Based on the literature study, this research found that pappasang not only functions as a provision for safety and smoothness in fishing, but also contains moral values that can be applied in everyday life, including in the field of education.